Understanding what matters to patients in critical care: An exploratory evaluation. Issue 4 (15th July 2019) - Connelly, Christine; Jarvie, Lyndsey; Daniel, Malcolm; Monachello, Emma; Quasim, Tara; Dunn, Lelia; McPeake, Joanne
Abstract: Background: The delivery of person‐centred care is a key priority for managers, policy makers, and clinicians in health care. The delivery person‐centred care in critical care is challenging because of competing demands. Aims and objectives: The aim of this quality improvement project was to understand what mattered to patients on a daily basis within the critical care environment. It aimed to understand personal goals and what patients needed to improve their experience. This paper reports on the outputs from this quality improvement project. Design and Data Analysis: During each daily ward round, patients were asked "what matters to you today?" Outputs from this were entered into the Daily Goals Sheet, which is utilized for every patient in our critical care unit or in the nursing notes. Using Framework Analysis, prevalent themes were extracted from the patient statements documented. Results: A total of 196 unique patients were included in this analysis alongside 592 patient statements. Four broad themes were generated: medical outcomes and information, the critical care environment, personal care, and family and caregivers. Conclusion: The analysis of the data from this quality improvement project has demonstrated that, by asking a simple question within the context of a ward round, care can be enhanced and personalized and long‐term outcomes potentially improved. More research is required to understand what the optimal methods are of implementing these requests. Relevance to clinical practice: Two main recommendations from practice emerged from this quality improvement project: asking patients "what matters to you?" on a daily basis may help support the humanization of the critical care environment, and visiting and access by families must be discussed with patients to ensure this is appropriate for their needs.